Influência do fotoperíodo no crescimento e sobrevivência de póslarvas de piracanjuba Brycon orbignyanus (Valenciennes, 1849) (Osteichthyes, Characidae) - Reynalte-Tataje, David; Luz, Ronald Kennedy [UNESP]; Meurer, Samira; Zaniboni-Filho, Evoy; De Oliveira Nuñer, Alex Pires (My University, 2002)
This paper aims at studying the influence of photoperiod on the cultivation of Brycon orbignyanus (Valenciennes, 1849) (Osteichthyes, Characidae) post-larvae submitted to four treatments: 0L-24D (L=Light; D=Dark), 10 - L14D, 14L - 10D and 24L-0D, with 3 repetitions. Post-larvae measuring 7.8±0.7mm and weighting 3.5±0.8mg were distributed in 12 aquariums (10L), stocked with 12 post-larvae per aquarium. Fishes were fed daily with Artemia sp. nanplii, in 10 days experiment. A positive relationship between the survival rate (88.9±9.7%) observed in the treatment with 24 hours of luminosity, and the lowest (58.3±8.3%), in the treatment with 24 hours of darkness. No difference was showed (P>0.05) in the mean length and weight of the post-larvae, although there was greater heterogeneity among the post-larvae cultivated at the longer darkness period.
Influence of photoperiod on the growth and survival of piranjuba post-larvae Brycon orbignyanus (Valenciennes, 1849) (Osteichthyes, Characidae)
Keywords: Brycon orbignyanus; Cannibalism; Fish larvae; Photoperiod; animal experiment; animal food; aquatic environment; Artemia; cannibalism; controlled study; darkness; fish; larval development; light; luminance; measurement; nonhuman; photoperiodicity; survival rate; Animalia; Artemia sp.; Brycon; Characidae; Osteichthyes; Pisces; Vertebrata